Soil resource inventory, land capability and crop suitability assessment of Bantanahalli micro-watershed under semi-arid regions of Karnataka - ANILKUMAR, S. N.; DHUMGOND, PRABHUDEV; SATISH, A.; PARAMA, V.R. RAMAKRISHNA (Journal of Soil and Water Conservation, 2020)
A study was conducted in Bantanahalli micro-watershed with the objective of assessing crop suitability with field crops viz. maize, finger millet, pigeonpea, cotton and horticulture crops like sapota and guava using land capability classification (LCC) through Geographic Information System (GIS) techniques. Bantanahalli micro-watershed (Hanumanahalli sub-watershed, Jagalur block, Davanagere district, Karnataka) is located in 140 40’– 140 41’N Latitude and 760 14’– 760 17’E Longitude covering an area of 669 ha bounded by 5 villages (Sokke, Chikkabantanahalli, Gopalapura, Madikeripura and Gadimakunte). The land capability classes and sub-classes were assigned based on depth (cm), slope (%), erosion status based on scores, surface and sub-surface gravel (%) and soil texture of each physiographic unit. These assignments were translated into a land capability map. The LCC of the study area indicated that, out of 699 ha of micro watershed area, 388 ha was under class II with moderate limitation of soil (depth, gravelliness, texture salinity/alkalinity) and erosion, while 171 ha was under class III due to severe limitation of soil (depth, gravelliness, texture salinity/alkalinity) and erosion. The crop suitability of the various physiographic units indicated that 107 ha was ‘highly suitable’ for maize, finger millet and pigeonpea and only 75 ha in case of cotton. About 434 ha was ‘moderately suitable’ for maize and pigeonpea, however 452 and 253 ha of land was ‘moderately suitable’ for finger millet and cotton, respectively due to gravelliness and rooting depth limitation. In case of horticulture species like guava and sapota, 75 ha was ‘highly suitable’; while 254 ha was ‘moderately suitable’ due to limitation of rooting depth and gravelliness; and 212 ha was marginally suitable due to severe gravelliness (35-60%) and restricted rooting depth (upto 50cm). Based on the study, the farmers could grow the suggested crops based on the land capability and soil suitability criteria, and attain maximum productivity and profitability under semi-arid Vertisols in south India.